Improving the Community's Economy Through Development Strategy at the Department of Trade, Manpower, Cooperatives and Small and Medium Enterprises - Vaguita, Mercya; Oktaviane, Diga Putri; Yeni, Hilda Oktri; Utama, Hendri Budi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The goal of this research is to improve the community’s economy through development strategy at the Department of Manpower Trade, Cooperatives, and Small and Medium Enterprises (UMKM) in Padang Pariaman Regency affected by the Covid-19 pandemic, and especially after the economic crisis. This study is a descriptive analysis that employs a qualitative method and relies on both primary and secondary data. In this study, informants were chosen using a purposive sample strategy that was based on certain features. The interviews, observations, and documentation studies using reliable and accurate sources are used to acquire data. The method and source triangulation are two techniques for assessing the veracity of data. While this data analysis approach employs data processing, data analysis, data reduction, and producing conclusions. According to the findings of this study, the strategy used to improve the community's economy can be seen through four indicators: (1) creation of a business climate for UMKM; (2) making integrated information; (3) establishment of a consulting and business development center; and (4) joint marketing system.